Improving the Quality of English Language Teaching And Learning - Sugiono, Sugiono (Universitas Nurul Jadid, 2020)
This is a literature study on how to improve the quality of English language teaching and learning. Teaching, in general, can give one daily an unbelievable roller coaster ride from the depths of total frustration to the heights of incredible rewards. Teaching is a profession that is given little respect and lots of criticism. English language teaching and learning is an educational process. It requires great preparation and implementation to maintain the interaction between teacher and students. Apart from this, the teacher needs to be skillful in identifying the needs that should be fulfilled and the objectives which should be achieved. Teacher perspective needs to orient itself to the teaching and learning activities that cover selection on the instructional materials being inline with the instructional objectives, approaches, methods, techniques, and suitable tasks and exercises. The study indicates that good English teaching and learning is tied not only to the subject matter in hand but also to the perspective of teaching that upholds the learner-oriented standpoint. It is strongly suggested that English language teaching and learning needs to do more on psycho-motoric domains, in the sense that it encourages students to do more practice in their learning.This is a literature study on how to improve the quality of English language teaching and learning. Teaching, in general, can give one daily an unbelievable roller coaster ride from the depths of total frustration to the heights of incredible rewards. Teaching is a profession that is given little respect and lots of criticism. English language teaching and learning is an educational process. It requires great preparation and implementation to maintain the interaction between teacher and students. Apart from this, the teacher needs to be skillful in identifying the needs that should be fulfilled and the objectives which should be achieved. Teacher perspective needs to orient itself to the teaching and learning activities that cover selection on the instructional materials being in line with the instructional objectives, approaches, methods, techniques, and suitable tasks and exercises. The study indicates that good English teaching and learning is tied not only to the subject matter in hand, but also to the perspective of teaching that upholds the learner-oriented standpoint. It is strongly suggested that English language teaching and learning needs to do more on psycho-motoric domains, in the sense that it encourages students to do more practice in their learning.